PENGARUH MODEL PEMBELAJARAN SPONTANEOUS GROUP DISCUSSION (SGD) PADA MATERI SISTEM EKSKRESI TERHADAP HASIL BELAJAR SISWA KELAS VIII SMPN 1 BATANG KAB. JENEPONTO - Arpina, Pipi; Taufiq, Ainul Uyuni; Ismail, Wahyuni (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze the effect of the Spontaneous Group Discussion (SGD) learning model on students’ learning outcomes in the topic of the excretory system. A quantitative approach was employed using a quasi-experimental design with a nonequivalent control group. The research sample consisted of two eighth-grade classes at SMPN 1 Batang, Jeneponto Regency, selected through purposive sampling. Each class comprised 35 students, assigned as the experimental and control groups. Data were collected using a learning outcomes test and analyzed using an independent samples t-test. The results showed that the mean posttest score of the experimental class was 76.14, which was higher than that of the control class, which obtained a mean score of 67.57. The statistical analysis yielded a Sig. (2-tailed) value of 0.000 < 0.05, indicating that the Spontaneous Group Discussion (SGD) learning model had a significant effect on improving students’ learning outcomes in the topic of the excretory system.